HISTORICAL CIRCULATION OF OTTOMAN TURKEY: FROM DYNASTIC TO REPUBLICAN SYSTEMS OF GOVERNMENT - Syihabuddin, Muhammad; Kholil, Ahmad (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
This article explores the historical circulation of Ottoman Turkey, highlighting the significant transition from a dynastic system of government to the establishment of the Turkish Republic in 1923. The Ottoman dynasty, which was originally a vast and influential empire, underwent dramatic changes during the 20th century. The main focus was on the post-World War I period when radical reforms were implemented to address internal and external challenges. This analysis covers socio-political aspects, tracing the changes that overhauled the structure of the feudal empire into a modern republican state. The method used is by using a method of literature study or library research related to historical or other similar themes. Based on the theory of the History of Islamic Civilization. As for data collection analyzing historical texts, collecting relevant data, and describing them. The results of this paper reveal that: First, every Kingdom will inevitably experience triumphs and setbacks, for a civilization is inseparable from it. Second, Ottoman Turkey was one of the influential dynasties of world civilization, and it was also crowned as the heir to the Islamic caliphate. Third, the Ottoman Turks underwent significant changes in terms of culture, socio-politics, economy, and others. The setback he experienced led to the secularization of Turkey which began as a dynastic state or caliphate into a republic. This was none other than triggered by the political factors of power that were in the hands of Mustafa Kemal Atatürk.